2011
DOI: 10.4049/jimmunol.1001920
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloides ratti Infection Induces Expansion of Foxp3+ Regulatory T Cells That Interfere with Immune Response and Parasite Clearance in BALB/c Mice

Abstract: To escape expulsion by their host’s immune system, pathogenic nematodes exploit regulatory pathways that are intrinsic parts of the mammalian immune system, such as regulatory T cells (Tregs). Using depletion of Treg mice, we showed that Foxp3+ Treg numbers increased rapidly during infection with the nematode Strongyloides ratti. Transient depletion of Tregs during the first days of infection led to dramatically reduced worm burden and larval output, without aggravation of immune pathology. The transient absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 59 publications
7
80
0
Order By: Relevance
“…In this setting, it was necessary to additionally interfere with other regulatory pathways by application of anti-CTLA-4 (27) or anti-GITR mAb (26) to improve resistance. Consenting with this study, we have shown that the depletion of Treg in Strongyloides ratti-infected BALB/c DEREG mice increased resistance to infection only if performed during the first days of infection, whereas depletion at later time points had no beneficial impact (50). Addressing this possibility, we also rule out a contribution of such secondary regulatory mechanisms induced by the presence of natural Treg during the first days of infection, as transient depletion of Treg during the first days of infection did not restore the L. sigmodontis-induced suppression of OT-II T cell proliferation at day 17 p.i.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, it was necessary to additionally interfere with other regulatory pathways by application of anti-CTLA-4 (27) or anti-GITR mAb (26) to improve resistance. Consenting with this study, we have shown that the depletion of Treg in Strongyloides ratti-infected BALB/c DEREG mice increased resistance to infection only if performed during the first days of infection, whereas depletion at later time points had no beneficial impact (50). Addressing this possibility, we also rule out a contribution of such secondary regulatory mechanisms induced by the presence of natural Treg during the first days of infection, as transient depletion of Treg during the first days of infection did not restore the L. sigmodontis-induced suppression of OT-II T cell proliferation at day 17 p.i.…”
Section: Discussionmentioning
confidence: 99%
“…These cells are able to control both Th2 and Th1 type immune responses [17]. Helminth infection can increase the frequency of Treg cells in mice [18,19], and in man an increase of Treg cells has been observed in Strongyloides infection in patients coinfected with HTLV-1 [20] as well as in hookworm-infected patients [21]. Furthermore, it has been shown that Treg cells can modulate the immune response in Mycobacterium bovis bacille Calmette-Guerin (BCG)-vaccinated individuals [22,23] and in patients with active TB [24].…”
Section: Introductionmentioning
confidence: 99%
“…Second, we compared the PBMC response by flow cytometry rather than by using diluted whole blood for the bead array assay. These two differences may explain the difference in response to ESAT6/CFP10 stimulation.Helminth infections are largely associated with Th2 immune responses [5], and few studies have shown that helminth infection can be associated with an increase of regulatory T cells (Tregs) [18,23,25,35,36]. In this study we analyzed the frequency of CD4 + FoxP3 + T cells.…”
mentioning
confidence: 99%
“…The depletion of Tregs in DEREG mice immediately after infection with S. ratti resulted in the expression of protective immunity (28), but the depletion of Tregs using anti-CD25 antibody during T. spiralis infection results only in increased Th2 responses without affecting parasite burden. However, the ablation or blockade of both IL-10 and TGF-␤ (presumably from a non-Treg source) does increase resistance to the parasite (25).…”
Section: Cd25mentioning
confidence: 99%